The sphericity of erythrocytes and its communication with biochemical, hemostasis and rheological by properties of blood at the patients with coronary disease and arterial hypertension - Y. I. Pivovarov; T. Y. Kurilskaya; A. S. Sergeyeva; L. B. Koryakina (Acta Biomedica Scientifica, 2013)
The aim of the work was to study the peculiarities of the influence of bloodfactors on the development of spherocytosis in patients with coronary disease and arterial hypertension. The study involved 30 patients with coronary disease and 24 patients arterial hypertension with the study of their clinical status and biochemical parameters of blood, hemostasis, blood cell analysis. It was found that the increase in the pool spherocytic cells in patients with arterial hypertension were associated with increased nitric oxide production, while in patients with coronary disease spherocytosis was due to an increase in the concentration of reactive oxygen metabolites.